Penerapan UTAUT untuk Memahami Akseptansi Mahasiswa terhadap Inovasi Cicilan Buku Berakad Murabahah - Izza Syafira Amalia; M. Ruslianor Maika (Department of Islamic Economics, IPB University, 2020)
The increasing interest of the Muslim community in Indonesia in the consumption of goods and services labeled halal has certainly made all things with a halal perspective appear. Fintech (financial technology) as a form of digitization of the rapid development of technology is also used in the financial sector. The focus discussed in this study is the obligation of students to have books and how the website innovation system works using the murabaha contract. This study uses a phenomenological approach by conducting interviews with 40 students of the Muhammadiyah University of Sidoarjo who have used and made transactions on the IjabQabul.id website. The data obtained from the interviews were reprocessed using the Atlas.ti software. The results showed that from the IjabQabul.id website, students were quite helped by the facilities provided, such as payment methods that could be made online or collectively as well as payment methods that could be made in installments. Additions and feature enhancements are also expected by users to be added to the website.